A Multidimensional Framework of Collaborative Groups’ Disciplinary Engagement - Rogat, Toni Kempler; Hmelo-Silver, Cindy E.; Cheng, Britte Haugan; Traynor, Anne; Adeoye, Temitope F.; Gomoll, Andrea; Downing, Brenda K (Frontline Learning Research, 2022)
Abstract This research is aimed at developing novel theory to advance innovative methods for examining how collaborative groups progress toward productively engaging during classroom activity that integrates disciplinary practices. This work draws on a situative perspective, along with prior framings of individual engagement, to conceptualize engagement as a shared and multidimensional phenomenon. A multidimensional conceptualization affords the study of distinct engagement dimensions, as well as the interrelationships of engagement dimensions that together are productive. Development and exploration of an observational rubric evaluating collaborative group disciplinary engagement (GDE) is presented, leveraging the benefits of observational methods with a rubric specifying quality ratings, enabling the potential for analyses of larger samples more efficiently than prior approaches, but with similar ability to richly characterize the shared and multidimensional nature of group engagement. Mixed-methods analyses, including case illustrations and profile analysis, showcase the synergistic interrelations among engagement dimensions constituting GDE. The rubric effectively captured engagement features that could be identified via intensive video analysis, while affording the evaluation of broader claims about group engagement patterns. Application of the rubric across curricular contexts, and within and between lessons across a curricular unit, will enable comparative studies that can inform theory about collaborative engagement, as well as instructional design and practice.